Implementasi Pendekatan Kolaboratif melalui Model Project-Based Learning (PjBL) dalam Menanamkan Karakter Sosial Siswa SD - Agung Setyawan; Devi Amalia Fajri; Fatihatur Rahmaniyah; Badruddin (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This classroom action research investigates the implementation of a collaborative Project-Based Learning (PjBL) model to enhance the social character of fourth-grade students at SDN Banyuajuh 5, Bangkalan. The study involved 25 students and employed a project titled "Composing Seblak Topping Based on Fractional Sequences," which integrated mathematics with a local culinary context to create authentic learning experiences. The primary objective was to analyze how a structured collaborative PjBL approach fosters social character development, including cooperation, empathy, responsibility, and conflict-resolution skills. Results demonstrated a significant improvement in students' collaborative activities and social character indicators. Observations revealed that while initial stages exhibited interpersonal conflicts and uneven participation, structured heterogeneous grouping and targeted teacher facilitation successfully guided students toward more constructive interactions and shared responsibility. The project's contextual and student-centered design proved crucial in maintaining high engagement and providing a meaningful platform for practicing social values. The study concludes that the integration of a collaboratively structured PjBL model, characterized by intentional grouping, contextual projects, and the teacher's role as a socio-emotional facilitator, is highly effective in holistically developing elementary students' social character alongside academic competencies. This approach offers a practical operational model for integrating character education into core academic subjects. For future application, it is recommended to develop more structured observational rubrics for social skills and to allocate sufficient time for in-depth project work to maximize collaborative depth.